Entrepreneurial strategy, resources acquisition and nascent venture performance in Malaysia - Rusnifaezah, Musa (2019)
The stage of emergence is found to be most crucial stage in entrepreneurship studies. The Harvard Business School research shows that 75 percent of all start-ups fail, while in Malaysia, researchers found out the rate of failure among the bumiputera, where the majority are Malay entrepreneurs, is the highest. This study aimed to investigate the nature of relationship that exists between entrepreneurial orientation, entrepreneurial bricolage and nascent venture performance in Malaysia. Furthermore, this study intended to examine the moderating effects of resources acquisition (government assistance programs and online social networking adoption) on the relationship between entrepreneurial strategies and nascent venture performance. This study employed the quantitative approach of research and the survey method was used to conduct the study on 184 Malay-owned nascent ventures in Malaysia. The data was analysed with the SPSS v.20 statistical technique. The correlation analysis indicated that all the factors have a significant positive effect on nascent venture performance. The regression analysis further revealed that entrepreneurial bricolage and proactiveness significantly influence nascent venture performance while innovativeness and risk taking of entrepreneurial orientation are not significant to nascent venture performance. The hierarchical regression analysis was utilized to examine the moderating effect. Meanwhile, government assistance programs only have moderating effects on the relationship between proactiveness and performance of nascent venture in Malaysia. These findings have demonstrated why new businesses cannot survive until the maturity stage of business development. This study justifies that the engagement between academicians, ministries, the government and the entrepreneurs in developing a new business model for nascent ventures is necessary. Using configuration theory, future research can extend the nascent venture performance context by examining the holistic aspects, consisted of; characteristics of the entrepreneurs, resources of the nascent entrepreneurs, environment, and organizing activities (management).